The possible contribution of 129I in the drinking water and food supply to the nodular formation of thyroid tissue - Dogru, O; Dogru, M; Aygen, E; Camci, C; Kirkil, C; Canbazoglu, C; Sahin, S (Lippincott Williams & Wilkins, 2005)
Nodular formation of the thyroid tissue can occur as a result of exposure to radiation. The nodular goiter is a common disease seen in the city of Elazig and its surroundings, in the eastern part of Turkey. A prospective study was conducted in an effort to identify the role of I-129 in drinking water supply. Specimens obtained from nodular and normal thyroid tissue during surgery and also water specimens were counted by nuclear spectrometric system. I-129 radioactivity in nodular tissue was noted to be higher compared to normal tissue and the difference was statistically significant (p < 0.05). There was no statistically significant difference (p > 0.05) between I-129 radioactivity in the water supply and tissue obtained from the patients who have malignant or benign nodular lesions. These results support that the I-129 radioactivity level in the water supply is one of the risk factors of the nodular formation of the thyroid tissue in the eastern part of Turkey.
Keywords: I-129; thyroid; water; uptake; radionuclide